Molecular differentiation of Salmonella Gallinarum and Salmonella Pullorum by RFLP of fliC gene from Brazilian isolates - Paiva,JB (2009)
Although Salmonella Pullorum and Salmonella Gallinarum cause different diseases in poultry, they are very similar. Both are non-motile and present the same somatic antigenic structure. They are differentiated by biochemical tests. Certain atypical strains are very difficult to distinguish. They do not produce the expected results when dulcitol and ornithine descarxboxylase tests are performed. Therefore, additional tests could be helpful. Many studies have chose the part I of the gene that encodes flagellin (fliC) to differentiate serotypes. Most Salmonella strains have two structural genes (fliC and fliB) that encode flagellins. Non-motile strains generally present these structural genes, but are not able to build a functional flagellum. It was demonstrated that enzymatic restriction of the amplified fliC gene using Hinp1I enzyme can differentiate SG from SP. In the present study, this method was adopted to analyze 14 SP and 22 SG strains, including some strains with atypical results in biochemical tests assessing the utilization of dulcitol and ornithine. The results showed that all SG strains were broken by the enzyme, whereas the 14 SP strains were not.